2019
DOI: 10.1523/jneurosci.1566-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Tiam1 is Critical for Glutamatergic Synapse Structure and Function in the Hippocampus

Abstract: Mounting evidence suggests numerous glutamatergic synapse subtypes exist in the brain, and that these subtypes are likely defined by unique molecular regulatory mechanisms. Recent work has identified substantial divergence of molecular composition between commonly studied Schaffer collateral synapses and perforant path-dentate gyrus (DG) synapses of the hippocampus. However, little is known about the molecular mechanisms that may confer unique properties to perforant path-DG synapses. Here we investigate wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 67 publications
(87 reference statements)
3
36
2
Order By: Relevance
“…The report that a same Neuroligin4 mutation can generate either ID or high-level ASD supports such subtle changes (67). Similarly, some protein complexes may integrate only a given form of a protein, as it is the case for TIAM1 in glutamatergic synapses from entorhinal cortex (39).…”
Section: Discussionmentioning
confidence: 87%
“…The report that a same Neuroligin4 mutation can generate either ID or high-level ASD supports such subtle changes (67). Similarly, some protein complexes may integrate only a given form of a protein, as it is the case for TIAM1 in glutamatergic synapses from entorhinal cortex (39).…”
Section: Discussionmentioning
confidence: 87%
“…Sanger sequencing confirmation could not be performed. De novo frameshift deletions in TIAM1 have been reported in three cases of autism thus far (Kosmicki et al, 2017), and mouse models investigating this gene has shown it plays a role in learning and memory in the hippocampus (Kojima et al, 2019; Rao, Kay, & Herring, 2019). The inframe insertion occurs in a well conserved region of the gene (CCR percentile = 96.35) (Havrilla, Pedersen, Layer, & Quinlan, 2019) while the gene is predicted to be intolerant of LoF variation (pLI = 0.96), it seems to tolerate missense variation (Zmiss = 1.7).…”
Section: Resultsmentioning
confidence: 99%
“…Instead, cultured neurons form indiscriminate synaptic connections regardless of their endogenous connections or cell type. The hippocampus, for example, has discrete regions of neuronal subtypes such as CA3 and CA1 pyramidal neurons and dentate granule neurons, and it has been increasingly appreciated that there is pathway-specific regulation that functionally differentiates these synapses 5 , 18 21 . Our novel approach allows for keeping the endogenous circuitry of synapses intact by utilizing hippocampal slices.…”
Section: Discussionmentioning
confidence: 99%
“…Highly specific, efficient, and quantitative methods currently exist for studying the influence of postsynaptic proteins on glutamatergic synapse function in the mammalian central nervous system. For example, viral and biolistic approaches may be used to restrict genetic manipulations to postsynaptic neurons, and the consequences of such manipulations may be measured by electrophysiological recordings from individual transduced/transfected postsynaptic neurons during electrical stimulation of unmodified presynaptic neurons 1 5 . However, comparable methods are sorely lacking for the study of proteins regulating presynaptic glutamatergic synapse function.…”
Section: Introductionmentioning
confidence: 99%